Garnet-biotite geothermometry of a pelitic gneiss from the Lutzow-Holm Complex in Skallen, East Antarctica: Constraints on retrograde metamorphism - Ikeda, Takeshi (National Institute of Polar Research, 2004)
P(論文) A garnet-rich pelitic gneiss was examined to estimate retrograde conditions of the Lutzow-Holm Complex in Skallen, East Antarctica. Porphyroblastic grains of garnet show a chemical zoning of an outward decrease in Mg/Fe, and include biotite, plagioclase and quartz. Local depletion in Mg/Fe of garnet is recognized where garnet is in contact with biotite occurring as inclusions and in the matrix. A pair of garnet-biotite geothermometry and garnet-plagioclase-sillimanite-quartz (GASP) geobarometry were applied for garnet rim and matrix biotite that are not in contact with each other, which demonstrates a retrograde condition of 5.6 kbar and 760℃. Pairs of garnet and adjacent biotite yield temperatures of ca. 660℃ at a nominal pressure of 6 kbar irrespective of whether biotiteoCcurs in the matrix or as inclusions, which represents the closure temperature for the exchange reaction between garnet and biotite. departmental bulletin paper